2012
DOI: 10.1073/pnas.1208866110
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type–specific roles of Na + /K + ATPase subunits in Drosophila auditory mechanosensation

Abstract: Ion homeostasis is a fundamental cellular process particularly important in excitable cell activities such as hearing. It relies on the Na + /K + ATPase (also referred to as the Na pump), which is composed of a catalytic α subunit and a β subunit required for its transport to the plasma membrane and for regulating its activity. We show that α and β subunits are expressed in Johnston's organ (JO), the Drosophila auditory organ. We knocked down expression of α subunits (ATPα and α-like) and β subunits (nrv1, nrv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 45 publications
1
80
0
Order By: Relevance
“…(Na þ /K þ )-ATPase, an electrogenic pump is responsible for maintaining the balance of Na þ and K þ in almost all animal cells. Na þ /K þ -ATPase is critical to a variety of physiological processes like osmoregulation, cell volume regulation, transport of certain amino acid and sugar and maintenance of membrane excitability (Ianowski and O'Donnell, 2004, Verma and Tapadia, 2014, Roy et al, 2013. Direct correlation of Na þ /K þ -ATPase levels and Na þ concentration was rather surprising in the present study, but it is in agreement with earlier reports where reduced levels of (Na þ /K þ )-ATPase resulted in reduced Na þ (Davis et al, 1995;Verma and Tapadia, 2014).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…(Na þ /K þ )-ATPase, an electrogenic pump is responsible for maintaining the balance of Na þ and K þ in almost all animal cells. Na þ /K þ -ATPase is critical to a variety of physiological processes like osmoregulation, cell volume regulation, transport of certain amino acid and sugar and maintenance of membrane excitability (Ianowski and O'Donnell, 2004, Verma and Tapadia, 2014, Roy et al, 2013. Direct correlation of Na þ /K þ -ATPase levels and Na þ concentration was rather surprising in the present study, but it is in agreement with earlier reports where reduced levels of (Na þ /K þ )-ATPase resulted in reduced Na þ (Davis et al, 1995;Verma and Tapadia, 2014).…”
Section: Discussionsupporting
confidence: 94%
“…(Na þ / K þ )-ATPase is a channel protein conserved from lower to higher organisms and plays a very important function in regulation of ionic balance in the cells (Roy et al, 2013). In adult and 3rd instar MTs, (Na þ /K þ )-ATPase has been reported to localize to the basolateral surface (Torrie et al, 2004;Verma and Tapadia, 2014), but due to absence of any report in 1st instar, we observed the expression of (Na þ /K þ )-ATPase in these larval MTs first.…”
Section: Expression Of Ecr-a B1 and B2 In Mtsmentioning
confidence: 99%
“…S2), to acoustic trauma and measured SEPs. Na + /K + ATPase is expressed in JO scolopidia where it likely regulates ion homeostasis (23). We hypothesized that mutant heterozygote JO neurons would be more severely affected by constitutive activity driven by the trauma stimulus, and demonstrate a higher sensitivity to trauma-induced metabolic stress.…”
Section: Physiological/behavioral Responses To Trauma In Control Stramentioning
confidence: 99%
“…Although evoked potential amplitudes were restored after 7 d, the latency of these potentials did not fully recover and we found significant changes in JO neural mitochondrial morphology. We also tested mutant flies with a reduced copy number of nervana 3 (nrv3) encoding a Na + /K + ATPase β subunit expressed in JO neurons (23). We hypothesized that compromised JO ionic homeostasis would confer susceptibility to noise trauma.…”
mentioning
confidence: 99%
“…The protein has been extensively studied in various organisms such as humans and drosophila, highlighting its importance in maintaining normal neuronal functions in an organism. Mutational studies and targeted knockdown studies have revealed that perturbations in the Na/K ATPase can lead to severe dysfunction in behavior, neuronal excitability, and defects in auditory mechanosensation (Roy et al, 2013), visual and motor sensory system (Palladino et al, 2003). Molecular characterization of the protein in gambiae is yet to be described.…”
Section: Overview Of Identified Proteinsmentioning
confidence: 99%